Синтез и исследование кремнийорганических покрытий, полученных из плазмы положительного столба тлеющего разряда в потоке аргона - Зуза, Даниил Александрович (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
The results of experiments on remote plasma-chemical deposition of organosilicon polymer coatings are discussed. The activation processes of hexamethyldisiloxane molecules occur in the positive column region. The main operating modes of the plasma-chemical system were found and the chemical structure of polymer coatings was investigated.